Bridging the Gapbetween Work and Education in Vocational Education and Training. A study of Norwegian ApprenticeshipTraining Offices and E-portfolio Systems - Hæge Nore; Leif C. Lahn (International Journal for Research in Vocational Education and Training (IJRVET), 2014)
This article explores the effect that the use of e-portfolios initiated and organized by apprenticeshiptraining offices has had on the learning processes and assessment practices of apprentices in Norwegian vocational education and training. Although these intermediate structures have the potential to bridge the gapbetween work and education, they seem to maintain a system of two parallel learning arenas. However, the article summarizes the innovative effects of these transformations as supportive structures for expansive apprenticeship. The study is based on data from a national project on quality assessment, which is supported by documentary evidence from e-portfolios in three different trades: plumbing, industrial mechanics and sales.
Keywords: 330; apprenticeship; boundary-crossing; e-portfolios; training offices; training agencies; innovation